2002
DOI: 10.1001/archneur.59.5.781
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Drug–Induced Bone Loss in Young Male Patients Who Have Seizures

Abstract: Long-term AED therapy in young male patients who have seizures causes significant bone loss at the hip in the absence of vitamin D deficiency. Dual-energy x-ray absorptiometry scanning of the hip is useful in identifying patients who are particularly susceptible to rapid bone loss while taking AEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
3
12

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(132 citation statements)
references
References 27 publications
3
114
3
12
Order By: Relevance
“…According to WHO criteria, 63, 5% of the patients had a diagnosis of osteopenia / osteoporosis in at least one of the sites measured. This incidence is higher than uncontrolled studies reported in the literature 6,11,12 . Because of the cross-sectional nature of the present study, it was not possible to know if the bone loss is specifically related to the use of AEDs or if there are other reasons for the differences appreciated in this study.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…According to WHO criteria, 63, 5% of the patients had a diagnosis of osteopenia / osteoporosis in at least one of the sites measured. This incidence is higher than uncontrolled studies reported in the literature 6,11,12 . Because of the cross-sectional nature of the present study, it was not possible to know if the bone loss is specifically related to the use of AEDs or if there are other reasons for the differences appreciated in this study.…”
Section: Discussioncontrasting
confidence: 54%
“…We have demonstrated significant abnormalities of bone metabolism, characterized by reduced BMD, reduced 25OHD, and increased AP. Previous studies have related these findings to chronic use of AEDs 5,6,11,12 . Serum levels of calcium and PTH were normal and similar to the control group.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Redução na densidade mineral óssea (DMO) tem sido demonstrada em usuários de valproato, uma DAE que não é metabolizada no fígado. A fisiopatologia das anormalidades ósseas decorrentes do valproato ainda é incerta, mas alguns autores sugerem que o mecanismo possa ser a ação direta da droga nos osteoblastos e/ou perda, por meio da urina, de cál-cio induzida pela toxicidade renal do valproato (10). Todavia, a maior parte dos autores acredita que as novas DAE não indutoras hepáticas interferem menos no metabolismo ósseo, embora haja uma necessidade de estudos adicionais para que se comprove essa afirmação (6).…”
Section: Dae Metabolismo Mineral óSseo E Fraturas óSseasunclassified